The evaluation of environmental learning support materials : a case study of the AAWARE teacher's guide - Glover, Dawn (Rhodes University, Faculty of Education, Department of Education, 2006)
This evaluative case study investigates the use of a specific learning support materials (LSMs) package, Animal Awareness for World and Regional Education (AA WARE), in the natural sciences, intermediate phase. Schools with access to the resource were canvassed through questionnaires to assess overall use in relation to distribution via workshop versus hand delivery, class size, availability of alternate LSMs and lastly the level of exposure to the distributing organisation. Three case studies were undertaken at three different schools. Data was generated through observations and interviews with the teacher undertaking the lesson observed. The aim of the case studies was to gain greater insight into AAWARE in practice and the factors that facilitated the use of the resource by these teachers. The research indicates that while AAWARE has overcome some inhibitors of resource use, its potential within Outcomes-Based Education (OBE) and the Revised National Curriculum Statements (RNCS) has not been achieved so far, except in a few isolated cases. Factors enabling the use of the resource are its user-friendly design, availability in all three languages spoken by the majority of Western Cape learners and the integration with education policy. Workshops, although not necessary for the utilisation of AA WARE in part, could enhance the integrated nature of the resource and introduce teachers to the potential of using the resource as an entire unit as opposed to a collection of separate lesson plans. A relationship is seen between exposure to the distributing organisation, the personal interest in wildlife of the teacher and the use of AAWARE. Finally recommendations are provided to increase the use of AA WARE. It is suggested that the resource undergoes a more effective alignment to RNCS content (RNCS policy was not an issue) now that RNCS implementation is completed. Further workshops should be offered in the use of AA WARE. Lastly a long-term strategy should be developed to enthuse schools and teachers about the intentions, goals and appropriateness of the resource.
Keywords: Environmental education -- South Africa -- Western Cape; Environmental education -- Curricula -- South Africa -- Western Cape; Teaching -- Aids and devices -- South Africa -- Western Cape